Clinical feasibility of panintestinal (or panenteric) capsule endoscopy: a systematic review. Issue 7 (July 2021) - Cortegoso Valdivia, Pablo; Elosua, Alfonso; Houdeville, Charles; Pennazio, Marco; Fernández-Urién, Ignacio; Dray, Xavier; Toth, Ervin; Eliakim, Rami; Koulaouzidis, Anastasios
Abstract : In recent years, panintestinal capsule endoscopy (PCE) with double-headed capsules has been used to perform complete, single-sitting exploration of both small bowel and colon in different clinical conditions. Double-headed capsules for colonic examination (CCE) have been exploited first in this setting, followed by newer generations of capsules (i.e. PillCam Crohn, PCC) specifically engineered for this purpose. The aim of this study was to evaluate the feasibility of PCE in the form of a systematic review. We performed a comprehensive literature search to identify papers in which CE was specifically used for a PCE of the gastrointestinal tract. Data on CE, bowel preparation regimen, rate of cleanliness and completeness, and data on transit times were analyzed. The primary outcome was to assess the feasibility of a whole-gut exploration with CE. Sixteen ( n = 16) studies including 915 CE procedures with CCE1 ( n = 134), CCE2 ( n = 357) and PCC ( n = 424) were included. 13/16 studies were performed in the setting of Crohn's disease. Cleanliness and completeness rates were acceptable in all studies, ranging from 63.9% and 68.6% to 100%, respectively. In conclusion, PCE is a feasible technique, although further structured studies are needed to explore its full potential. Abstract : Supplemental Digital Content is available in the text.